Nano-scale characterization of advanced gate stacks using transmission electron microscopy and electron energy loss spectroscopy - Li, Xiang (2010)
This thesis introduces the characterization methodologies which bridge microscopic properties of material change with macroscopic characteristics of a semiconductor device. The objective is to decode the nature of the insulator-to-conductor transition of the gate dielectrics when a leakage path is formed, and understand its impact on device performance and reliability. The oxygen deficiency is proposed to be the dominating defect responsible for the progressive degradation of the ultrathin gate oxide. The silicon nano-cluster transforms the percolation path into a stable configuration and pushes the post-breakdown conduction to a higher level. It is shown that the metal atoms in the gate electrode can migrate into the percolated high-κ dielectrics and form a conductive filament, and therefore reduce its post-breakdown reliability margin. In contrast, the percolation path can be partially repaired for fully silicided gate by controlling the oxygen diffusion and/or metal filamentation. Moreover, the interfacial dipoles are identified to be the origin of the negative flatband voltage shift for sub-stoichiometric TiNx gate.